Sull'infanzia: itinerario di alcuni testi esemplari - Daniela Sarsini (Firenze University Press, 2012)
The essay deals with the images of childhood that have established between eighteenth and nineteenth century, through the reading of some exemplar texts, that have become classics (like Rousseau, Becchi, Cambi, Trisciuzzi, Schérer-Hocquengham, Postman and Savater). The purpose is highlight how the epistemological status of childhood is changed during the last centuries in the european culture.